Microbial Communities Associated With Long-Term Tillage and Fertility Treatments in a Corn-Soybean Cropping System - Srour, Ali Y.; Ammar, Hala A.; Subedi, Arjun; Pimentel, Mirian; Cook, Rachel L.; Bond, Jason; Fakhoury, Ahmad M. (Frontiers in Microbiology, 2020)
Tillage and fertilization are common practices used to enhance soil fertility and increase yield. Changes in soil edaphic properties associated with different tillage and fertility regimes have been widely examined, yet the microbially mediated pathways and ecological niches involved in enhancing soil fertility are poorly understood. The effects of long-term conventional tillage and no-till in parallel with three fertility treatments (No fertilization, N-only, and NPK) on soil microbial communities were investigated in a long-term field study that was established in the 1970s. We combined high-throughput microbial community classification and community-level functional and ecological assembly to discern principles governing tillage and fertility practices’ influence on associated soil microbiomes. MiSeq amplicon libraries targeting bacteria, fungi, fusaria, and oomycetes were generated, sequenced and analyzed at the taxonomy and trait levels. The tillage effect was more prominent as a factor affecting the composition of soil microbial communities than the fertilizer effect. The analyzed data uncovered specific networks of metabolic pathways and distinct ecological guilds associated with each treatment. Notably, ecological guilds featuring arbuscular mycorrhizae, mycoparasites, and nematophagous fungi were favored in no-till soils, while fungal saprotrophs and plant pathotrophs dominated in tilled soils. Copiotrophic bacteria and fusarium species were favored under conventional tillage and in the presence of fertilizers. The analysis of the metagenomes revealed a higher abundance of predicted pathways associated with energy metabolism, translation, metabolism of cofactors and vitamins, glycan biosynthesis and nucleotide metabolism in no-till. Furthermore, no specific pathways were found to be enriched under the investigated fertilization regimes.